Identification of ortho catechol-containing isoflavone as a privileged scaffold that directly prevents the aggregation of both amyloid β plaques and tau-mediated neurofibrillary tangles and its in vivo evaluation - Son, Seung Hwan; Do, Ji Min; Yoo, Ji Na; Lee, Hyun Woo; Kim, Nam Kwon; Yoo, Hyung Seok; Gee, Min Sung; Kim, Jong Ho; Seong, Ji Hye; Inn, Kyung Soo; Seo, Min Duk; Lee, Jong Kil; et al. (Bioorganic Chemistry, 2021)
In this study, polyhydroxyisoflavones that directly prevent the aggregation of both amyloid β (Aβ) and tau were expediently synthesized via divergent Pd(0)-catalyzed Suzuki-Miyaura coupling and then biologically evaluated. By preliminary structure–activity relationship studies using thioflavin T (ThT) assays, an ortho-catechol containing isoflavone scaffold was proven to be crucial for preventing both Aβ aggregation and tau-mediated neurofibrillary tangle formation. Additional TEM experiment confirmed that ortho-catechol containing isoflavone 4d significantly prevented the aggregation of both Aβ and tau. To investigate the mode of action (MOA) of 4d, which possesses an ortho-catechol moiety, 1H-15N HSQC NMR analysis was thoroughly performed and the result indicated that 4d could directly inhibit both the formation of Aβ42 fibrils and the formation of tau-derived neurofibrils, probably through the catechol-mediated nucleation of tau. Finally, 4d was demonstrated to alleviate cognitive impairment and pathologies related to Alzheimer's disease in a 5XFAD transgenic mouse model.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Catechols; Disease Models, Animal; Drug Design; Isoflavones; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurofibrillary Tangles; Neuroprotective Agents; Peptide Fragments; Protein Aggregates; tau Proteins; Alzheimer's disease; Amyloid β; Catechol; Polyhydroxyisoflavone; Tau